EVALUASI MANAJEMEN PEMELIHARAAN ARSITEKTUR, MEKANIKAL, DAN ELEKTRIKAL PADA GEDUNG HOTEL X DI KOTA PADANG - Sufran, Hanif; Maulana, Muhammad Ilham; Hidayati, Rahmi; Misriani, Merley; Jumyetti, Jumyetti (Jurusan Teknik Sipil Universitas Bangka Belitung, 2023)
Based on the results of field inspections, damage to architectural, mechanical, and electrical components was found in several rooms of Hotel X in the city of Padang, West Sumatra, Indonesia. Lack of maintenance is one of the causes of damage to hotel building components. Good maintenance management can reduce repair activities that cost more due to injury. This study aims to evaluate the maintenance management of hotel buildings that have been carried out so far. In this study, researchers conducted surveys and interviews about hotel maintenance management. The survey and discussions focused on the hotel's Standard Operating Procedures (SOPs) for each component reviewed. After obtaining the hotel SOP, the researcher analyzed it by comparing the hotel SOP with the Minister of Public Works Regulation No.24/PRT/M/2008 as a standard in the implementation of building maintenance. From the results of the conformity calculation carried out, the conformity results in each component are architectural components with an average conformity result of 72.38%, mechanical parts with an average conformity result of 88.89%, and electrical components with an average conformity result of 77.78% of a maximum weight of 100%. This percentage of conformity weight shows that the hotel's maintenance management concerning the Ministerial Regulation is quite good. Still, to further optimize maintenance activities, it is necessary to plan better standard operating procedures, cost planning, and maintenance schedules to support implementing Hotel X building maintenance in the future.